Role of LNG-IUS in abnormal uterine bleeding - Mani, Poonam; Chhabra, Nikshima; Chaudhary, Neeta; Setia Chhabra, Satuti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Abnormal uterine bleeding (AUB), is deﬁned as a change in any or a combination of frequency, duration, or amount of bleeding, is a common gynecological complaint that affects 10‑30% of reproductive‑aged women and constitute about one‑third of all outpatient gynecological visits. Mirena is a hormonal intrauterine device classified as a long-acting reversible contraceptive method. Women with heavy menstrual blood loss, the LNG‑IUS can normalize blood flow. This high level of levonorgestrel in the endometrium induces dramatic effects leading to the unique mode of contraceptive and therapeutic action of the LNG‑IUS. Initially developed to decrease the risk of expulsion of the intrauterine contraceptive device by reducing myometrial contractility. Methods: This study was a prospective interventional study conducted in the department of Obstetrics and Gynaecology, Muzaffarnagar Medical College, Muzaffarnagar, Uttar Pradesh, over a period of 6 months. MIRENA insertion was done in outpatient department. The effectiveness of device was assessed by reduction in amount of bleeding in case of abnormal uterine bleeding and in the form of subjective symptomatic improvement along with improvement in quality of life. Record of menstrual pattern. Pictorial Blood loss Assessment Chart was used to assess the amount of blood loss in each cycle. The women were called for follow-up after 1 month, then 3 months, and then 6 months and asked regarding the relief they have obtained from the antecedent menstrual complaints. Hemoglobin (Hb) estimation was done on the subsequent visits. Results: The mean subjective percentage reduction of blood loss reduced from 13.64% at the first visit to 72.16% at 6th month and the mean Hb level in our study before treatment was 6.8 which increased to 9.8 at the end of 6 month. Conclusions: The levonorgestrel-releasing intrauterine system-mirena, provides an incredible nonsurgical alternative in treatment of menorrhagia which is reversible and spares fertility.